2022
DOI: 10.1186/s12891-022-05580-7
|View full text |Cite
|
Sign up to set email alerts
|

Potential association of bone mineral density loss with cognitive impairment and central and peripheral amyloid-β changes: a cross-sectional study

Abstract: Background There is some evidence in the literature that older adults with cognitive impairments have a higher risk for falls and osteoporotic hip fractures. Currently, the associations between bone health and cognitive health have not been extensively studied. Thus, the present cross-sectional study aims to investigate the relationship between markers of bone loss and cognitive performance in older adults with and without osteopenia as well as older adults with cognitive impairments (i.e., Alz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Previously, it has been suggested that cognitive decline may affect the bone remodelling process [ 36 ]. Indeed, Zhang et al [ 21 ] showed a significant decrease in BMD in subjects with Alzheimer’s disease compared to NCF participants and a positive correlation between BMD and scores obtained in the Minimal Mental State Examination (MMSE) scale. In addition, the receiver operator characteristic curve analysis indicated that this densitometric variable could be used to distinguish cognitive impairment participants from NCF individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, it has been suggested that cognitive decline may affect the bone remodelling process [ 36 ]. Indeed, Zhang et al [ 21 ] showed a significant decrease in BMD in subjects with Alzheimer’s disease compared to NCF participants and a positive correlation between BMD and scores obtained in the Minimal Mental State Examination (MMSE) scale. In addition, the receiver operator characteristic curve analysis indicated that this densitometric variable could be used to distinguish cognitive impairment participants from NCF individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a previous meta-analysis showed that obesity and a higher body mass index (BMI) may be associated with an increased risk of dementia [ 20 ]. Some data also suggested that bone mineral density (BMD) is reduced in cognitively impaired individuals [ 21 , 22 ], but this has not been confirmed in other studies [ 23 ]. Furthermore, the underlying mechanisms for the association between cognition and body composition and densitometric parameters are not yet fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Estrogen may play an important role in preventing osteoporosis and cognitive function. It delays neuronal apoptosis and atherosclerosis, inhibits the formation of amyloid b protein, prevents hyperphosphorylation of tau protein, reduces oxidative stress response in the brain, and improves brain cell metabolism ( Jett et al, 2022 ; Zhang et al, 2022 ). The findings of Loskutova et al (2010) suggested that BMD is reduced in both men and women in the early clinical stages of Alzheimer’s disease, and low BMD may be useful for identifying participants with Alzheimer’s disease or cognitive decline.…”
Section: Discussionmentioning
confidence: 99%
“…As described in our previous study ( 18 ), the mediation analysis was utilized to determine whether serum neurotrophins could mediate the association between depressive behaviors and knee pain, which is based on a standard three-variable mediation model ( 19 ). Covariates were age, sex, pain of duration, BMI, and treatment types.…”
Section: Methodsmentioning
confidence: 99%